(untitled) (Research, Society and Development, 2023)
This scientific article presents an analysis of the water quality of the Grajaú River, in the state of Maranhão. The objective was to understand if the river water complies with the parameters established by the regulatory bodies for human consumption. Samples were collected at different points along the river, considering bathing areas and regions with greater human influence. The parameters evaluated included pH, turbidity, dissolved oxygen, ammonia, nitrite, nitrate and orthophosphate. The results showed that the pH was within the potability standard, however the concentration of dissolved oxygen in some points was below the established minimum value. This indicates concern about water quality in these areas, as the low concentration of dissolved oxygen can negatively affect aquatic life. In addition, the presence of untreated domestic sewage and solid waste in the river was observed, mainly in spas. Considering these results, it is necessary to adopt measures to preserve and improve the quality of water in the Grajaú River, seeking to protect aquatic ecosystems and guarantee the well-being of the population. Continuous monitoring of water quality is essential to ensure an adequate and safe supply of this resource. Therefore, comprehensive and in-depth studies on water quality in different regions are needed, taking specific factors into account, in order to develop effective management strategies and public policies to ensure long-term water security.